2017
DOI: 10.4103/ccd.ccd_1173_16
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick and sharp instruments injuries among Brazilian dentistry students

Abstract: Background:The occurrence of occupational accidents is common among students and dentists. The present study is aimed to evaluate the prevalence and characteristics of needlestick and sharp instrument injuries among dentistry students.Materials and Methods:A documentary research was carried out with data being obtained from the analysis of 137 medical records of injuries caused by needlestick and sharp instruments occurring in the period from 2012 to 2016 and were analyzed regarding the characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…For the score, the value of 1 was placed for each correct answer and 0 for an incorrect one, following the methodology used in the study of Liege et al [ 10 ]. The mean and the standard deviation were evaluated on knowledge, attitudes, and practices regarding the infection control in undergraduate stomatology students of the UPSJB where the values of 2.74 (2.16), 3.59 (0.88), and 3.59 (1.73), respectively, were found, thus noting that the score of the level of knowledge was the lowest, compared to the level of attitudes and practices that were higher with respect to the preclinical, clinical, and internship cycles ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the score, the value of 1 was placed for each correct answer and 0 for an incorrect one, following the methodology used in the study of Liege et al [ 10 ]. The mean and the standard deviation were evaluated on knowledge, attitudes, and practices regarding the infection control in undergraduate stomatology students of the UPSJB where the values of 2.74 (2.16), 3.59 (0.88), and 3.59 (1.73), respectively, were found, thus noting that the score of the level of knowledge was the lowest, compared to the level of attitudes and practices that were higher with respect to the preclinical, clinical, and internship cycles ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, according to a recent study, the places where most injuries occur are the fingers of the hand, followed by arms, palm, thigh, leg, foot, and cheeks [ 9 ]. These injuries occur when having a small space, when making sudden movements on the part of the patient or of the own practitioner, and when using sharp and cutting materials [ 10 ]. The knowledge about the etiological agents has evolved in such a way that the treatments and related factors have allowed to establish measures to reduce the health risks [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zagade et al ( 2020) identified the incidence rate of sharps injury to be 22.23% amongst dentistry students. Musekene et al (2020) reported 41% of dental students had sustained a sharps injury and similarly Fernandes et al (2017) found an incidence rate of 43%. There is very limited data within the literature regarding sharps injuries involving paramedicine students.…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted by Kumar among dental students and interns in India found that 81.9% were aware that an active vaccine to prevent hepatitis B transmission was available. Only 50% of the students showed a positive opinion towards recording data on hepatitis B in the patient's file [28]. The study conducted by Li in China pointed out that 89.43% of the dental undergraduates had good or excellent knowledge on HBV transmission, illustrating the good results of education on infection control before clinical practice [16].…”
Section: Assessing the Perception Of The Level Of Knowledge About The...mentioning
confidence: 99%
“…Kumar (India, 2015) [28] found significant differences between groups (interns, finalyear students, and third-year students) in what concerns knowledge and preventive practices, with higher scores for the third-year students, followed by final-year students and then interns. This suggests that students may forget some of the notions learned about infection control; consequently, it is necessary to re-educate them in this regard at a time closer to graduation.…”
Section: Assessing the Perception Of The Level Of Knowledge About The...mentioning
confidence: 99%